Mechanical behavior of colonic anastomosis in experimental settings as a measure of wound repair and tissue integrity - Ekmektzoglou, Konstantinos A (World journal of gastroenterology : WJG, 2006)
AIM： To determine the mechanical properties of anastomotic colonic tissue in experimental settings and therefore give a measure of wound healing. METHODS： Thirty-six male Wistar rats were used as experimental models of anastomotic tissue integrity. On the 5^th post-operative day, the tensile strength was measured by application of an axial force, providing a quantitative measure of anastomotic dehiscence and leakage. RESULTS： Diagrams of the load as a function of the time [P = P （t）] and of the displacement also as a function of time [△s = △s （t）] were recorded for each test, permitting the design of the load versus the displacement diagram and thus providing significant data about the critical values of anastomotic failure. Quantitative data were obtained concerning the anastomotic strength of both control specimens （healthy rats）, as well as specimens from non-healthy rats for comparison. CONCLUSION： This experimental model provides an excellent method of measuring anastomotic strength. Despite the relative small number of specimens used, this method provides an accurate way of measuring wound repair. More experimental measurements need to be performed to correlate emerging tensile strength values to anastomotic failure.